The Effectiveness of Using a Dictionary of Balaghah Terms in Improving Undergraduate Students’ Understanding of Balaghah - Mukhlisin; Syarifuddin; Miftachul Taubah (Al-Fakkaar, 2026)
This study aims to examine the effectiveness of using the Dictionary of Balaghah Terms in improving students' understanding of Balaghah courses. The low understanding of abstract Arabic terminology is often a major obstacle for students in mastering this discipline. This study uses a quantitative approach with a One Group Pretest-Posttest pre-experimental design. The population as well as the sample in this study were all 5th-semester students of the Arabic Language Education Study Program at Yudharta Pasuruan University, totaling 9 students (saturated sampling). Data were collected through test instruments and analyzed using the Shapiro-Wilk normality test and Paired Sample T-Test using SPSS. The results showed a significant increase in the mean score from 53.78 at the pre-test to 89.11 at the post-test. The results of the hypothesis test showed a significance value of < 0.001 (p < 0.05), which means there is a significant influence of the use of the dictionary on students' understanding. In addition, the Cohen’s d value of 2.154 indicates a level of effectiveness in the very large (Large) category. It can be concluded that the Dictionary of Balaghah Terms is a very effective learning medium for improving students' cognitive competence in understanding Balaghah concepts deeply.